A narrative review of cancer molecular diagnostics: past, present, and future. Issue 4 (31st December 2022) - Yao, Jinjuan; Zhai, Qihui (Jim)
Abstract : Along with the advances in cancer genomics and the development of targeted therapies, the field of molecular diagnostics has undergone rapid evolution to meet the growing needs associated with patient care. Here, we review the past, present, and possible future of molecular diagnostics, including technologies and testing principles, to provide a comprehensive landscape of molecular diagnostic technologies, testing platforms, and applications. This review is based on the US Food and Drug Administration publications, the National Comprehensive Cancer Network guidelines, and the peer-reviewed English literature published between 2003 and 2021. We conclude that molecular diagnostics has changed dramatically during the past two decades. Next-generation sequencing–based comprehensive genomic profiling has replaced single-gene/single-locus testing for simultaneous detection of mutations, copy number alterations, structural variants, and mutational signatures to facilitate cancer diagnosis, prognosis prediction, targeted therapies, and immunotherapies. Laboratory-developed tests and companion diagnostics approved by the US Food and Drug Administration both play important roles in cancer patient management.